Sistema de autenticación para el control del acceso a internet en el distrito de educación 13d06 Bolívar - Junín - Buste Zambrano, José Orlando (2017)
In order to optimize the internet service in the different departments of the Education District 13D06 Bolívar - Junín, an Authentication System was used to control, monitor and register users. To ensure availability of internet access, we used the PfSense system which is built on FreeBSD free distribution update 2.2.6 x64 bits. In which Proxy services packages were installed for the control and was accompanied by the application WireShark 2.0.1 for the monitoring and traffic of the network. The implementation of the system was performed taking into account minimum aspects of operations, availability of technological equipment and institutional requirements that were incorporated into the server. The authentication system contributed to the control of unauthorized access by users, requesting a registration of username and password to enter the network of the Institution. In this way an appropriate and personalized distribution of the Institutional bandwidth was made for each department and departmental heads regardless of their functions. The performance of the processes in lines improved by 90%, with the authentication system and the redesign of the network, based on the implementation of the access control to the same. The restrictions and rules of the network administrator improved the connectivity of communication equipment avoiding the saturated use of the same; which allowed the satisfaction of each users and administrative staff, providing a quality service under the Ecuadorian constitution.